Design and fabrication of components of dye sensitised solar cells - Msane, Gugu (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
In recent decades there has been increasing global concern about the sustainability of our use of fossil fuels, which has led to increased interest in carbon"“free sustainable renewable sources such as solar energy. Dye sensitized solar cells (DSSCs) are a cheap and clean technology that harnesses solar energy efficiently and convert it to electrical energy. A DSSC consists of a transparent working electrode coated with a dye-sensitized mesoporous film of nanocrystalline particles of semiconductor e.g. TiO2, an electrolyte containing a suitable redox couple and a platinized counter electrode. All the components of the DSSCs play vital roles in controlling the performance of the cell. The synergy of these components of the cells also needs to be investigated to optimise their interaction and create efficient and stable DSSCs. The information gathered from this investigation can give insight on how to improve the efficiencies of DSSCs. In this research study the semiconductor, transparent conducting layer and sensitizer were designed, optimized one at a time and their effect on the overall efficiency of the DSSCs studied. In this way it was easy to observe the effect of the individual components on the efficiency of the DSSCs. The conventional DSSCs usually use TiO2 as a semiconductor. In this research TiO2 was doped with cerium (Ce) to enhance its optical properties by reducing the band gap. A series of Ce-doped TiO2 with Ce content ranging from 0.1 to 1 mol % were successfully synthesized by an acid catalyzed sol-gel method, and their performance as the photoanodes of dye-sensitized solar cells (DSSCs) was investigated. Ce doping resulted in a red shift in the absorption of the TiO2 indicating narrowing of the band gap. The band gap first narrowed with increase in concentration of dopant up until 0.9 % dopant concentration. After this optimum doping concentration the band gap widened again. DFT calculations showed that Ce doping introduces Ce4f impurity states located just below the conduction band resulting in band gap narrowing. Ce content (0.9%) doped TiO2 photoanodes improved the performance of DSSCs with a conversion efficiency of 2.11% compared to 0,21% for the one with a pure TiO2 under 1 sun, AM1.5. Graphitised/TiO2 nanocomposites were also used a semiconductor to slow down recombination of electrons and holes in the cells. Electrophoretic deposition (EPD) was used to deposit graphitised/TiO2 nanocomposites onto an FTO electrode for application as photoelectrode in dye-sensitized solar cells (DSSCs). An enhanced power conversion efficiency (PCE) of 2.25% was observed for the 0.5 wt% graphene oxide/TiO2 (GO/TiO2) based DSSC which was higher than that of the conversion efficiency of pure TiO2 nanoparticles (i.e. 0.52%). Graphene oxide led to high migration of photoinduced electrons to the conduction band of the collection electrode and inhibition of charge carriers recombination resulting in enhanced photoconversion efficiency. A GO content above 0.5 % resulted in a reduced transparency leading to a decrease in the PCE. 0.5 wt % GO/0.9 Ce"“TiO2 Ce based DSSC showed a slightly enhanced efficiency of 2.45%. 0.5 rGO/TiO2 based DSSCs had a high efficiency than 0.5 rGO/TiO2 due to improved conductivity of rGO nanosheets and suppressed recombination of charge carriers. To cut down DSSC production costs a silver wire network transparent conducting polyethylene electrodes was fabricated and used as an indium tin oxide (ITO) alternative substrates in DSSCs. The transmittance of the AgNW network was 82 % which is comparable to ITO substrates. Titanium oxide (TiO2) films on the AgWN/PET substrates were obtained using the electrophoresis method. These substrates were sensitised and used to fabricate a dye sensitised solar cell. From the measured current"“voltage or I-V characteristic under AM1.5 illumination of the formed DSSC using AgWN substrates, an open circuit voltage (VOC) of 0.377 V, a short circuit current (ISC) of 0.0067 mA and a fill factor (FF) 25.7 % with an efficiency of 0.00862 % were obtained from a cell of 0.075 cm2 working area. The stability of the cell improved when a room temperature ionic liquid electrolyte was used. Gold nanofiber transparent electrodes were also prepared by the electrospinning techniques and used as an alternative to indium tin oxides substrates. Transparent conducting gold nanofiber (AuNF) transparent conducting electrodes were fabricated by using a low"“cost electrospinning process and used as photoelectrodes for DSSCs. TiO2 was deposited on these electrodes by using an electrospray method. DSSC using AuNF as transparent electrodes had a power efficiency of 0.52%, compared to devices made with FTO electrodes (1.48%). DSSCs. Versatile dyes with increased spectral response, stability and suppressed recombination of holes and electrons were synthesised and used as a sensitizers for DSSCs. The boron dipyrrin (BODIPY) chromophore was combined with a carboxy coumarin moiety to create donor"“acceptor (dyad) system dyes. Regenerative dyad dyes were formed through covalently linking a porphyrin chromophore to a manganese(II) ion through bridging ligands. These chromophores and also porphyrin and BODIPY dyes were used as sensitisers for DSSCs. The regenerative dye based DSSCs showed a photoconversion efficiency of 4.09% which was higher than the efficiency of the parent porphyrin (2.57%). The enhanced efficiency was attributed to the manganese bypridine cluster in the ZnTPP"“Mn bpy supramolecule which acted as an electron donor to the photo-oxidized porphyrin continuously regenerating the porphyrin and preventing its decay.
Keywords: Dye-sensitized solar cells